Danish Finds of Mammoth (Mammuthus primigenius (Blumenbach)) Stratigraphical position, dating and evidence of Late Pleistocene environment - Aaris-Sørensen, Kim; Petersen, Kaj Strand; Tauber, Henrik (Danmarks Geologiske Undersøgelse Serie B, 1990)
A catalogue of all known remains of mammoth in Denmark is presented, comprising 125 finds. Half of the mammoth material is molars, which are morphologically referred to Mammuthus primigenius (Blumenbach), a third is tusk, and the rest is bone fragments. 14 specimens of mammoth have been C-14 dated. 13 samples have ages from older than 40 000 to ca 21500 C-14 years B.P., and one sample gave an age of ca 13200 C-14 years B.P. As the skeletal material is redeposited, these dates at the same time give maximum ages of the glacial deposits in which they are found. On the basis of this evidence the glacial development during the Weichselian is reviewed. An ice-free period from before 45000 B.P. to around 20 000 years B.P. is indicated. A mammoth tusk from the Tirstrup sandur on Djursland, dated to 13240 +760/-690 B.P., marks an important stage in the ice retreat in Denmark, and shows that the mammoth re-immigrates after the maximum expansion of the Weichselian ice. Remains of other Late Pleistocene vertebrates are also mentioned. On the basis of floral and faunal remains the environmental changes during the Late Pleistocene are then reconstructed. The ice-free period in the Middle Weichselian was characterized by a steppe biome, which may appropriately be termed the mammoth steppe. This Weichselian environment seems to be incomparable to any environment known today.